Challenges for European Tourist-City-Ports: Strategies for a Sustainable Coexistence in the Cruise Post-COVID Context - María J. Andrade (MDPI AG, 2021)
In recent years, cruise tourism has increased the negative effects caused by touristification in many European port cities. Despite this, these cities are in a great competition to be a destination, a tourist-port. Cruise tourism has come to stay, and a steady growth can be expected in a post-COVID-19 scenario, but at what cost? The tourist-port demands highly effective planning answers occurring simultaneously, and the global pandemic crisis provides a buffer of time to seek best practices, combining the expected economical (re)development with social, environmental, and cultural sustainability. This paper proposes five different strategies that contribute to finding a sustainable coexistence between tourist ports and their cities. To this end, trans-scalar strategies developed in previous research from different disciplines have been studied and categorized in a port-city context, in order to provide a holistic viewpoint on the measures carried out to maximize the benefits and limit the negative impacts of cruise tourism on cities.